Competition Among Manufacturers in Technological Innovation in the Market with Delayed Information (European Journal of Pure and Applied Mathematics, 2014)
The search for information in memory of technological competition  process in the market is analysed using techniques widespread in  biomathematics. Here we examined the effects that delayed  information causes in choosing strategies process on the part of  manufacturers to supplant a technology by introducing an alternative  one. A differential-equation system with delays is presented to  describe the dynamics of an endogenous model with memory.  Situations of competition in which the market has several  manufacturers using the same technologies and are in competition are  analyzed.  Conditions for stability and existence of periodic  oscilations by means of Hopf bifurcation is investigated.